Advances in selective catalytic oxidation of ammonia (NH3–SCO) to dinitrogen in excess oxygen: A review on typical catalysts, catalytic performances and reaction mechanisms. Issue 1 (February 2021) - Gao, Fengyu; Liu, Yuanyuan; Sani, Zaharaddeen; Tang, Xiaolong; Yi, Honghong; Zhao, Shunzheng; Yu, Qingjun; Zhou, Yuansong
Graphical abstract: This review summarizes the promising NH3 –SCO catalysts including noble metals, transition–metal oxides (typically, Cu–based composite oxides) and molecular sieves, and concludes the reaction routes of NH3 dehydrogenation, Eley-Rideal, Langmuir–Hinshelwood, Internal SCR and N2 – mechanism during the over–oxidation of ammonia. Highlights: Noble metals, transition–metal oxides and molecular sieves are summarized as NH3 –SCO catalysts. Reaction routes are proposed of NH3 dehydrogenation, Eley-Rideal, Langmuir–Hinshelwood, internal –SCR and N2 – mechanisms. Alternative catalytic systems are gratifyingly reviewed on promising Cu–based catalysts. Improving activity and selectivity are determined by surface oxygen coverage and reaction temperature. Future research trends are urgently addressed on work challenges in large–scale–up effects. Abstract: Various NH3 –SCO catalysts highly promising to reduce NH3 emission are summarized and classified considering of N2 –selectivity (SN2 ) at T100% (starting temperature for complete NH3 conversion) in previous scientific researches: noble metals (e.g. Ag°/Al2 O3, Pd/Ru–modified zeolite with SN2 >90% at T100% of 150–300 °C), transition–metal oxides (e.g. Fe–based, Ce–V compounds, SN2 >90% at T100% of 300–450 °C, except Cu–containing), molecular sieves (Fe– or/and Cu–modified ZSM–5 with ∼100% SN2 at T100% = 400 °C, meso/micro–porous Cu–modified SSZ, Beta, SAPO with N2 –selectivity >95% at 250–350 °C). The promising Cu–based catalysts gratifyingly include: (i) excellent noble–metals doped–CuO (CuO/RuOx, CuO–RuOx/Al–ZrOx, Ag–CuO, etc., almost 100% SN2 at T100% = 150–250 °C); (ii) translation (rare–earth) metals modified oxides (Cu–CeOx, Cu–FeOx, etc., almost 100% at ∼250 °C); (iii) CuO/Al2 O3 and/or CuAl2 O4, CuFe2 O4, etc., >95% at 300–350 °C); (iv) Cu–doped Mg, Al, Fe, Zn complex metal–oxides (90% N2 –selectivity at ∼450 °C). The NH3 –SCO catalytic oxidation products are strongly obeyed the differentiated reaction routes of NH3 dehydrogenation, N2 –, Langmuir–Hinshelwood, Eley-Rideal and internal -SCR mechanisms. Important ideas for hierarchical–controlling NH3 dehydrogenation should be given more attentions on improving both activity and selectivity that mainly determined by the surface oxygen coverage and also reaction temperature. Finally, future trends are urgently addressed on operating in a low–broad temperature range with simulating exhaust mixture-gases, imperatively considering the possible changes on designing the integrated structured catalysts and on testing large–scale–up effects typical for real flue gases.